2017
DOI: 10.1111/cdev.12790
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic‐Racial Identity and Friendships in Early Adolescence

Abstract: The current study examined how adolescents' ethnic-racial identity (ERI) informed the demographic diversity of their friendship network (Goal 1) and the extent of similarity between adolescents' and their friends' ERI (Goal 2). Participants were sixth and seventh grade students (N = 353; M = 11.88, SD = .73; 50% girls; 29% African American, 31% White, 13% Latino) in the Midwestern U.S. Results from longitudinal cross-lagged models (Goal 1) indicated that having more diverse friendships at T2 was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 65 publications
1
79
0
2
Order By: Relevance
“…Future research should use an adolescent-driven measure of parent and peer socialization. Recent research, however, has indicated that adolescent report of peer behaviors may be under or over estimated (Rivas-Drake, et al, 2017; Yip et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should use an adolescent-driven measure of parent and peer socialization. Recent research, however, has indicated that adolescent report of peer behaviors may be under or over estimated (Rivas-Drake, et al, 2017; Yip et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Although most attention is placed on the role of parents in ethnic socialization, peers serve as equally important socialization agents (Hu et al, 2012; Syed, 2012; Rivas-Drake, Umaña-Taylor, Schaefer, & Medina, 2017; Yip, Douglass, & Shelton, 2013). Ethnic socialization among peers is more likely to occur during adolescence when adolescents seek more autonomy from parents and are more influenced by peer relationships (Harris, 1995).…”
Section: Ethnic Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rivas‐Drake et al. () show that having more diverse friendships drives stronger exploration of ethnic–racial identity half a year later. In addition, Rivas‐Drake et al.…”
Section: Key Findingsmentioning
confidence: 99%
“…In addition, Rivas‐Drake et al. () show that in early adolescence friends become more similar to each other in ethnic identity exploration and resolution (influence effect in social network analysis). This influence effect was replicated in the study by Santos et al.…”
Section: Key Findingsmentioning
confidence: 99%